2003
DOI: 10.1177/039139880302600206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hollow Fiber Length on Solute Removal and Quantification of Internal Filtration Rate by Doppler Ultrasound

Abstract: Renal replacement therapy with dialyzers capable of enhanced internal filtration (IF) can be an alternative to standard hemodiafiltration, as it provides convective solute removal comparable to that of hemodiafiltration by a simple procedure. In this study, we clinically evaluated the effect of the hollow fiber length in the dialyzer, a crucial factor influencing the rate of IF, by comparing two commercial dialyzers (BS-1.6U, BS-1.6UL, Toray, Japan) which differed in the fiber length, but had the same surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Similarly, mass conservation for the flow of plasma proteins in the blood compartment gives: (14) which yields:…”
Section: Development Of a Semiempiricalmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, mass conservation for the flow of plasma proteins in the blood compartment gives: (14) which yields:…”
Section: Development Of a Semiempiricalmentioning
confidence: 99%
“…The interaction between these factors is rather complex and it involves nonlinear relationships resulting in different effects. In the past, experimental quantification of IF/BF was carried out in vitro by measuring the local concentration of a marker molecule [12] , by scintigraphic methods [13] , or by echo-Doppler blood velocity measurements [14] . But applying such methods systematically in vivo does not seem to be feasible, due to equipment complication and/or to the requirement of additional competencies.…”
mentioning
confidence: 99%
“…Obviously, dialyzer length effectively regulates dialysate pressure drops. In one study conducted to clarify the effect of dialyzer length on solute clearance, middle-to-large uremic molecules, such as 2M and alpha-1 microglobulin ( 1M), were shown to be better cleared by a 250 mm dialyzer than a 195 mm dialyzer (Sato et al, 2003). Dialysate pressure drop can also be manipulated by modulating membrane packing density.…”
Section: Factors Influencing Internal Hdfmentioning
confidence: 99%
“…Thus, changes in blood velocity along a dialyzer provide information on blood volume changes and on amounts of forward and backward filtration. In one study, the internal filtration rate of a 250 mm dialyzer was found to be 37.7 ml/min by Doppler ultrasonography, but only 11.1 ml/min for a standard 195 mm dialyzer (Sato et al, 2003). Doppler ultrasonography is straightforward, non-invasive, and easily used at bedside (Mineshima, 2011).…”
Section: Internal Filtration Quantificationmentioning
confidence: 99%
“…While several previous studies have estimated internal filtration rates for standard high-flux filters [17][18][19] , a similar quantitative assessment for the HRO filter class has not been performed. Therefore, the aim of this study was to quantify convective volumes for 2 HRO filters, Theranova 400 and Theranova 500 (Baxter International Inc., Deerfield, IL, USA), when used under typical HD operating conditions.…”
Section: Introductionmentioning
confidence: 99%